Systematic Evaluations of Tax Accounting Textbooks. - Horvitz, Jerome S.; Jensen, Herbert L. (The Accounting Review, 1979)
Abstract ABSTRACT: The objective of this paper is to utilize a taxonomy of cognitive skills to evaluate the comparative merits of textbooks on tax accounting presently used in the undergraduate curriculum. The taxonomy has been developed by a group of educational psychologists and can be expressed as a set of educationally useful objectives for student behavior. Because of its structure, the taxonomy of cognitive skills provides an appropriate explicit criterion for a comparative evaluation of tax texts. This approach to evaluation is illustrated using the opinions of a sample of tax instructors.